Development of quantitative therapeutic tool for motion disorder patients using Hill's equation and neuronal modelling of motor pathways - Ho, Desmond Wee Kiat (2011)
Studying the principles governing human movement can help us understand more about human locomotion which in turn can help to improve existing rehabilitation methods. Currently there is a lack of quantitative method to record improvements of patients with motion disorder undergoing treatment through rehabilitation or drugs intake. This project focused on two main objectives to provide a solution for the above. A close loop reflex system has been developed with the identification of a good mechanical model. The mechanical model was generated based on Hill’s equation and research comprising of theoretical and experimental analyses of interaction between motor and sensory control mechanisms had been carried out to formulate the reflex loop control system. Data and results generated proved that the mechanical model exhibit the actual mechanics and characteristics of muscle movements, thus made it suitable for the proposed reflex loop system. Doctors and physiotherapists will be able to use this reflex loop control system to quickly quantify physical improvement of patients with motion disorder usually cause by neural disease. The research can be enhanced with clinical trials to further prove the effectiveness of the control system. It is essential to collect more data on the different size of muscles and limbs, store them into a database and create a simple program to feed the data into the reflex loop. This will allow practitioners to work on a wider range of limbs movements.